Kinetics and Mechanism of Oxidation of Benzaldehyde by Benzimidazolium Fluorochromate in Aqueous Acetic Acid Medium - Sheik Mansoor, S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of benzaldehyde (BA) by benzimidazolium fluorochromate (BIFC) in aqueous acetic medium has been studied at 303 K. The reaction is first order with respect [BIFC], [BA] and [H+]. The reaction has been found to be catalyzed by H+ ions. To study the effect of structure reactivity relationships, some para-substituted benzaldehydes were subjected to oxidation by benzimidazolium fluorochromate at four different temperatures and thermodynamic parameters were calculated. The Exner plot showed that all the para-substituted benzaldehydes are oxidized by the same mechanism. The Hammett plot is linear with positive r values. The products of the oxidation are the corresponding acids. From the observed kinetic results a suitable mechanism has been proposed.